Interaction Phenomena to Be Accounted for Human-Induced Vibration Control of Lightweight Structures - Díaz, Iván M.; Gallegos, Christian A.; Ramírez Senent, José; Renedo, Carlos M. C. (Frontiers in Built Environment, 2021)
Inertial mass controllers, including passive, semi-active and active strategies, have been extensively used for cancelling human-induced vibrations in lightweight pedestrian structures. Codes to check the vibration serviceability and current controller design approaches assume that both excitation forces and controller forces are the same on a flexible structure and on a rigid structure. However, this fact may not be assumable since interaction phenomena arise even for moderately lightweight structures. Analyzing two case studies in this paper, interaction phenomena involved in the frequency-domain-based design of passive and active inertial mass dampers are discussed. Thus, a general vibration control problem including the interaction phenomena is set hereby. Concretely, this paper deeply discusses the following issues: (i) how the structure to be controlled is affected when human-structure interaction is presented for deterministic and stochastic conditions, (ii) the closed-loop transfer function of the controlled structure including a passive inertial mass damper, and (iii) the closed-loop transfer function of the controlled structure including an active inertial mass damper. In addition, the performed analysis considers the actuator dynamics and the actuator-structure interaction.